Effect of light sources on bond strength of different composite resins repaired with bulk-fill composite = Efecto del tipo de fuente luz en la resistencia adhesiva de distintas resinas compuestas reparados con una resina bulk-fill - Kiliç, Vahti
The aim of this study was to evaluate and compare the effects of different light sources on shear bond strength when bulk-fill composite was used for the repair of different composite resins. A total of 126 samples made from six resin composites with different properties were aged (thermal-cycling with 5000 cycle), exposed to the same surface treatments and adhesive procedure. Then, they were repaired with a bulk-fill composite. At the polymerization step, each group was divided into three subgroups (n=7) and light cured with a QTH light source for 40s and two different LED light sources for 20s. Subsequently, the specimens were aged in distilled water at 37 ºC for 4 weeks and then subjected to shear bond strength test. Then, the specimens were examined under a stereomicroscope to identify modes of failure and visualized by Scanning Electron Microscope. Data obtained from the study were analyzed using ANOVA and Tukey HSD Test (α=0.05). In all groups, the light curing units had an impact on shear bond strength (p<0.05). Among the study groups, the greatest bond strength values were observed in the specimens repaired using the LED and the specimens repaired with the QTH light curing unit had the lowest bond strength values. It was concluded that the content of composite resins and light curing units may influence bond strength of different composites repaired with the bulk-fill composite.